Information management, crisis and emergencies - Eito-Brun, Ricardo (Anuario ThinkEPI, 2008)
Emergency and crisis management professionals work in complex conditions. Information management is a key factor in ensuring the efficiency of their work. In this area of activity we can find numerous requirements for managing real-time information to coordinate the efforts of the different teams involved in these complex scenarios. These requirements include the identification and diffusion of alerts in response to actual or potential crisis, management of and access to logistic and geographical information, etc. This brief overview of some relevant information systems dedicated to emergency and crisis management (ReliefWeb and AlertNet) also addresses the use of open source software tools to organise and manage this information.
Keywords: Emergency and crisis management; Information services; Web portals; AlertNet; Reuters; ReliefWeb.